Introduction to Hospitality Management / John R. Walker, Josielyn T. Walker - Walker, John R.
Capturing the flavor and breadth of the industry, Introduction to Hospitality Management, Fourth Edition, explores all aspects of the field including: travel and tourism; lodging; foodservice; meetings, conventions and expositions; and leisure and recreation. Devoting six chapters to management, the text focuses on hospitality and management and uses first-person accounts, corporate profiles and industry morsels to foster a student's appreciation for the field. Throughout, author John R. Walker invites students to share this industry's unique enthusiasm and passion. The text is organized into five sections: the hospitality industry and tourism; lodging; restaurants, managed services, and beverages; recreation, theme parks, clubs, and gaming entertainment; and assemblies and event management. Each section includes insight from industry professionals, contains up-to-date information on career opportunities, and includes many examples illuminating current industry trends and realities. Extensively revised and updated, this edition contains new photos, new page layouts, and new coverage on topics ranging from sustainability to globalization.